2018
DOI: 10.1002/syn.22033
|View full text |Cite
|
Sign up to set email alerts
|

Effects of endogenous and exogenous D1/D5 dopamine receptor activation on LTP in ventral and dorsal CA1 hippocampal synapses

Abstract: Hippocampus is importantly involved in dopamine-dependent behaviors and dopamine is a significant modulator of synaptic plasticity in the hippocampus. Moreover, the dopaminergic innervation appears to be disproportionally segregated along the hippocampal longitudinal (dorsoventral) axis with unknown consequences for synaptic plasticity. In this study we examined the actions of endogenously released dopamine and the effects of exogenous D1/D5 dopamine receptor agonists on theta-burst stimulation-induced long-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 83 publications
2
22
0
Order By: Relevance
“…Together, these data indicate that 6x 1:1 t-LTP depends on D1/D2 receptor co-signaling whereas 6x 1:4 t-LTP is only dependent on D2 receptors, highlighting a novel and important role of D2 receptors in both types of t-LTP. This is at variance with the fact that most previous studies investigating DA-dependent conventional LTP at SC-CA1 synapses reported an eminent role of D1-like receptors in high frequency induced LTP forms (e.g., Hagena and Manahan-Vaughan, 2016;Papaleonidopoulos et al, 2018). However, our results are fully consistent with the previously described D2 receptor mediated enhancement of t-LTP in the prefrontal cortex (Xu and Yao, 2010), and the prominent role of D2 receptors in hippocampus-dependent learning (Nyberg et al, 2016).…”
Section: Figure 7: Differential Modulation Of Canonical and Burst Low Repeat T-ltp By Dopaminergic Signalingsupporting
confidence: 86%
See 1 more Smart Citation
“…Together, these data indicate that 6x 1:1 t-LTP depends on D1/D2 receptor co-signaling whereas 6x 1:4 t-LTP is only dependent on D2 receptors, highlighting a novel and important role of D2 receptors in both types of t-LTP. This is at variance with the fact that most previous studies investigating DA-dependent conventional LTP at SC-CA1 synapses reported an eminent role of D1-like receptors in high frequency induced LTP forms (e.g., Hagena and Manahan-Vaughan, 2016;Papaleonidopoulos et al, 2018). However, our results are fully consistent with the previously described D2 receptor mediated enhancement of t-LTP in the prefrontal cortex (Xu and Yao, 2010), and the prominent role of D2 receptors in hippocampus-dependent learning (Nyberg et al, 2016).…”
Section: Figure 7: Differential Modulation Of Canonical and Burst Low Repeat T-ltp By Dopaminergic Signalingsupporting
confidence: 86%
“…DA receptors in the brain are classified into D1-like receptors that include D1 and D5, and D2-like receptors that include D2, D3 and D4 (Missale et al, 1998). It has been shown that activation of D1/D5 receptors has a particularly strong effect on hippocampal synaptic efficacy (Dubovyk and Manahan-Vaughan, 2018;Papaleonidopoulos et al, 2018), and high repeat t-LTP in hippocampal neurons(see e.g., (Edelmann and Lessmann, 2011;Zhang et al, 2009). Moreover, D4 receptors are known to modulate NMDAR function in CA1 in vivo and ex vivo (Herwerth et al, 2012;Li et al, 2016).…”
Section: Distinct Dopaminergic Modulation Of Different Low Repeat T-ltp Protocols At Schaffer Collateral-ca1mentioning
confidence: 99%
“…Short-term dynamics of neuronal activity profoundly regulate neural information flow in local circuits ( Abbott and Regehr, 2004 , Jackman and Regehr, 2017 , Pariz et al, 2018 ) and neuromodulation represents a basic mechanism that determines or shapes information transfer between neural elements ( Ito and Schuman, 2008 ). Importantly, neuromodulatory actions of several neuromodulators may considerably differ along the septotemporal axis of the hippocampus, see examples in Malik and Johnston, 2017 , Dubovyk and Manahan-Vaughan, 2018 , Mlinar and Corradetti, 2018 , Papaleonidopoulos et al, 2018 ), and have significant implications in hippocampal physiology and pathology, discussed in Gulyaeva (2019 ). Neuromodulation is one aspect of the diversification in functional organization along the longitudinal axis of the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that the increased salience to facilitate consolidation into IC results from the synaptic potentiation induced by photostimulation of the VTA dopaminergic neurons. It is widely known that tonic and phasic dopaminergic release differentially modifies and modulates the synaptic strength and neuronal activity in many different structures, including the hippocampus, prefrontal, and insular cortices, to serve as a cellular mechanism to establish memory (Matsuda et al, 2006;Sheynikhovic et al, 2013;Rodríguez-Durán and Escobar, 2014;Otani et al, 2015;Navakkode et al, 2017;Papaleonidopoulos et al, 2018). In fact, findings support that brief exposure to a novel environment reduces the threshold to induce long-term potentiation.…”
Section: Discussionmentioning
confidence: 98%